2021
DOI: 10.3390/ijms22179344
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of MaTGA8 Transcription Factor in Banana and Its Defence Functional Analysis by Overexpression in Arabidopsis

Abstract: TGA transcription factor is a member of the D subfamily of the basic region-leucine zippers (bZIP) family. It is a type of transcription factor that was first identified in plants and is the main regulator in plant development and physiological processes, including morphogenesis and seed formation in response to abiotic and biotic stress and maintaining plant growth. The present study examined the sequence of the MaTGA8 transcription factor, the sequence of which belonged to subfamily D of the bZIP and had mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Effect of SA on BsTGAL6/BsCYP81Q expression and B. syzigachne resistance to mesosulfuron-methyl Because exogenous application with SA can modulate the expression of TGA genes (Lin et al, 2021;Moon et al, 2018), SA was used to examine the role of TGAL6 on BsCYP81Q expression and consequently on B. syzigachne resistance to mesosulfuronmethyl. SA was applied to the two-to three-leaf stage R and S B. syzigachne plants and expression of TGAL6 and BsCYP81Q was RT-qPCR measured at 0, 6, 12, and 24 h after treatment.…”
Section: Emsamentioning
confidence: 99%
“…Effect of SA on BsTGAL6/BsCYP81Q expression and B. syzigachne resistance to mesosulfuron-methyl Because exogenous application with SA can modulate the expression of TGA genes (Lin et al, 2021;Moon et al, 2018), SA was used to examine the role of TGAL6 on BsCYP81Q expression and consequently on B. syzigachne resistance to mesosulfuronmethyl. SA was applied to the two-to three-leaf stage R and S B. syzigachne plants and expression of TGAL6 and BsCYP81Q was RT-qPCR measured at 0, 6, 12, and 24 h after treatment.…”
Section: Emsamentioning
confidence: 99%
“…VvTGA8 overexpression in S. lycopersicum significantly improved the resistance to C. vitis and activated the expression of SlPR1 and SlPR2, further supporting the role of VvTGA8 in resistance to C. vitis (Figure 7). A study has shown that the overexpression of MaTGA8 from banana significantly enhances resistance to Fusarium oxysporum TR4 in A. thaliana [38]. In addition, TGA8 promotes root growth by promoting stem cell regeneration, meristem activity, and cell elongation in A. thaliana [27].…”
Section: Discussionmentioning
confidence: 99%
“…Referred to the method of Lin et al(2020), pCAMBIA-1300 was selected as the vector and EcorV was selected as the restriction site [17]. The recombinant expression vector pBWA(V)HS-miR160a was transformed into Agrobacterium tumefaciens strain GV3101 (Wuhan Biorun Biotechnology Co., Ltd., Wuhan, China) and then was transformed into Arabidopsis thaliana (Col-0) by in orescence infection.…”
Section: Mac-mir160a Overexpression Vector Construction and Arabidops...mentioning
confidence: 99%